Genetic and Structural Analysis of SARS-CoV-2 Spike Protein for Universal Epitope Selection. (3rd May 2022) - Markosian, Christopher; Staquicini, Daniela I.; Dogra, Prashant; Dodero-Rojas, Esteban; Lubin, Joseph H.; Tang, Fenny H.F.; Smith, Tracey L.; Contessoto, Vinícius G.; Libutti, Steven K.; Wang, Zhihui; Cristini, Vittorio; Khare, Sagar D.; et al.
Abstract: Evaluation of immunogenic epitopes for universal vaccine development in the face of ongoing SARS-CoV-2 evolution remains a challenge. Herein, we investigate the genetic and structural conservation of an immunogenically relevant epitope (C662–C671) of spike (S) protein across SARS-CoV-2 variants to determine its potential utility as a broad-spectrum vaccine candidate against coronavirus diseases. Comparative sequence analysis, structural assessment, and molecular dynamics simulations of C662–C671 epitope were performed. Mathematical tools were employed to determine its mutational cost. We found that the amino acid sequence of C662–C671 epitope is entirely conserved across the observed major variants of SARS-CoV-2 in addition to SARS-CoV. Its conformation and accessibility are predicted to be conserved, even in the highly mutated Omicron variant. Costly mutational rate in the context of energy expenditure in genome replication and translation can explain this strict conservation. These observations may herald an approach to developing vaccine candidates for universal protection against emergent variants of coronavirus.